Fortification of canton noodles with beta-carotene and iron from powdered malunggay (Moringa oleifera) leaves - de Veyra, Milanie Soledad L. (c2009)
Malunggay (Moringa oleifera) is known as excellent source of nutrients.
Sotech thesis.
Keywords: Malunggay; Moringa oleifera